2015
DOI: 10.1039/c4nj01906g
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition and cytostatic effects on human cancer cells by pyrazolone-enamines: a combined crystallographic, structural and computational study

Abstract: Interactions are possibly through hydrogen bonding of the pyrazolone ring and the hydroxyl, or the intercalation of conjugated plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…For decades, Schiff bases have been considered important ligands due to their coordination chemistry, and they can be easily prepared and linked with a different kind of metal ions 18 . Due to the existence of an amine group, analogous to the natural biological systems, Schiff bases show a crucial role in observing the conversion mechanism and racemization reaction in biological systems 19 – 25 . Schiff bases have been used for various essential biological activities including antitumor, anti HIV, antibacterial, antifertility activities, antimosquito larval, antiinflammatory, and anticancer 26 – 33 .…”
Section: Introductionmentioning
confidence: 99%
“…For decades, Schiff bases have been considered important ligands due to their coordination chemistry, and they can be easily prepared and linked with a different kind of metal ions 18 . Due to the existence of an amine group, analogous to the natural biological systems, Schiff bases show a crucial role in observing the conversion mechanism and racemization reaction in biological systems 19 – 25 . Schiff bases have been used for various essential biological activities including antitumor, anti HIV, antibacterial, antifertility activities, antimosquito larval, antiinflammatory, and anticancer 26 – 33 .…”
Section: Introductionmentioning
confidence: 99%
“…[150][151][152] They have been extensively used as key intermediates in organic synthesis [153][154][155] and as ligands in coordination chemistry, [156][157][158] and can be synthons in bioactive natural products. [16,[162][163][164][165][166][167][168][169][170][171][172] Ag reat deal of evidence has been collected by using various spectroscopic techniques such and X-ray analyses, showing that b-enaminones are stabilized in the tautomeric form A.T hus, the RAHB can be responsible for the observedu sual equilibrium shift towards the Z-isomer. [16,[162][163][164][165][166][167][168][169][170][171][172] Ag reat deal of evidence has been collected by using various spectroscopic techniques such and X-ray analyses, showing that b-enaminones are stabilized in the tautomeric form A.T hus, the RAHB can be responsible for the observedu sual equilibrium shift towards the Z-isomer.…”
Section: Synthesis Of B-enaminonesmentioning
confidence: 99%
“…[171] X-ray analysis showedt hat all of them adopted the RAHB-supported pyrazolone-enamine tautomeric form in the solid state. [171] X-ray analysis showedt hat all of them adopted the RAHB-supported pyrazolone-enamine tautomeric form in the solid state.…”
Section: Synthesis Of B-enaminonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Creaven et al, 14 reported that the coumarin-derived Schiff bases and their copper (II) complexes, were cytotoxic to the breast cancer-derived MCF-7 mammalian cell line, at concentrations which were comparable to the cytotoxic activity of the commercially used drug, mitoxantrone. Apart from this, there are most of the Schiff base shows a crucial role in observing the conversion mechanism and racemization reaction in biological systems [15][16][17][18][19][20][21] . Many study reports state that there is a wide number of Schiff bases have been used for various essential biological activities, including antitumor, anti-HIV, antibacterial, antifertility activities, antimosquito larval, anti-inflammatory, and anticancer [22][23][24][25][26][27][28][29] .…”
mentioning
confidence: 99%